DISTRIBUTION AND ABUNDANCE OF CRYPTOFAUNA FROM LIZARD ISLAND, GREAT BARRIER REEF - Hutchings, Patricia A.; Weate, Penny D. (Marine Research in Indonesia, 1977)
A series of replicate samples of dead coral reef habitats was collected across Yonge Reef on the outer and inner reef (back reef) and on fringing reefs around Lizard Island. Five categories of habitats were selected, branching, thin plates, high percentage of live coral, solid reef, rock with either a small surface area or a large surface area, and easily broken up. The surface area, volume, percentage cover of epifauna and flora, and biomass of cryptofauna were determined for each habitat. An estimate of the percentage of cavity space (i.e. available living space for cryptofauna) occurring in each habitat was made. The cryptofauna is dominated by polychaetes, molluscs, and sipunculans. Habitats on inner Yonge have a larger biomass of cryptofauna than similar habitats found on outer Yonge or on fringing reefs around Lizard Island. Differences in physical attributes of the habitat together with exposure and surrounding species of coral and sponges may be responsible for these differences.